Service quality monitoring and measurements in IMS networks - Mäkilä, Ville (fi=Turun yliopisto|en=University of Turku|, 2018)
This thesis focuses on service quality monitoring and measurement in IMS networks. Internet Protocol Multimedia Subsystem (IMS) is an architectural framework for telecommunications operators for providing services. Main emphasis is on real time communication services such as Voice over IP (VoIP) in IP communications systems. Real time communications over IP has common quality issues and the quality of those real time services need to be monitored. The objective of this study was to find solutions and tools to conduct service quality monitoring. The study was carried out by using selective literature review as research method. At first, IMS architecture was introduced and main components were identified. Also service quality and its characteristics in VoIP is discussed. Understanding the IMS system and VoIP service monitoring guided the selection of usable monitoring tools and solutions. The results suggest that understanding the service quality customers experience, it could be beneficial to focus on the performance of the IMS network and its elements. End-to-end service quality cannot be simply measured and visibility in terms of data is needed to other networks. However, there are monitoring tools that together can provide useful information about the performance of IMS network and experienced service quality.